Central America and the Dominican Republic Regional Assessment : Status of Disaster Risk Management in the Water Supply and Sanitation Sector--Policy Framework and Practice - World Bank (Washington, DC, 2015)
The purpose of this economic and sector work (ESW) is to support the Republic Forum for potable water and sanitation (FOCARD-APS) member countries in improving the resilience of water supply and sanitation (WSS) services. This report summarizes the findings from seven country-specific assessments carried out in 2013 and 2014 that characterize the national disaster risk management (DRM) and climate change adaptation (CCA) frameworks and efforts designed to reduce the vulnerability of WSS services to disasters and climate change. This activity also supports the World Bank strategy for enhancing DRM in Central America. This analytical effort is the result of a comprehensive participatory process that contributed to building the analytical capacities of the institutions that conform the FOCARD-APS’s regional thematic group (RTG) for DRM. It involved thorough document reviews and two rounds of country visits for data collection, as well as consultation with national and regional experts. The findings of all assessments were validated through national and regional workshops by the RTG-DRM. Regional learning exchanges and study visits were organized as part of this activity to provide policy makers with concrete examples of approaches and potential measures for addressing disaster risk challenges from a WSS service provision perspective and through a broader political and sectoral scope covering policy development, financing, capacity building, and institutional reform.